Subtle Variations in Surface Properties of Black Silicon Surfaces Influence the Degree of Bactericidal Efficiency - Chris M. Bhadra; Marco Werner; Vladimir A. Baulin; Vi Khanh Truong; Mohammad Al Kobaisi; Song Ha Nguyen; Armandas Balcytis; Saulius Juodkazis; James Y. Wang; David E. Mainwaring; Russell J. Crawford; Elena P. Ivanova (Nano-Micro Letters, 2018)
Abstract One of the major challenges faced by the biomedical industry is the development of robust synthetic surfaces that can resist bacterial colonization. Much inspiration has been drawn recently from naturally occurring mechano-bactericidal surfaces such as the wings of cicada (Psaltoda claripennis) and dragonfly (Diplacodes bipunctata) species in fabricating their synthetic analogs. However, the bactericidal activity of nanostructured surfaces is observed in a particular range of parameters reflecting the geometry of nanostructures and surface wettability. Here, several of the nanometer-scale characteristics of black silicon (bSi) surfaces including the density and height of the nanopillars that have the potential to influence the bactericidal efficiency of these nanostructured surfaces have been investigated. The results provide important evidence that minor variations in the nanoarchitecture of substrata can substantially alter their performance as bactericidal surfaces.